2017
DOI: 10.1007/s13197-017-2533-8
|View full text |Cite
|
Sign up to set email alerts
|

Cassava derivatives in ice cream formulations: effects on physicochemical, physical and sensory properties

Abstract: In the present study, the effects of derivatives of cassava, maltodextrin and bagasse, on the physicochemical, physical and sensory properties of ice creams were investigated. The content of cassava maltodextrin increased significantly the content of carbohydrate and total soluble solids and decreased lipids content. The effect of cassava bagasse was more pronounced than the maltodextrin on physical and sensory parameters. Increased percentage of cassava bagasse in formulation led to decrease of overrun, melti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Although the vegan formulations did not show a significant difference between them (P ࣘ 0.05), they differed from the traditional and lactose-free formulations, being below the required levels, with overrun values ranging from 41 and 42%. Lower overrun values were found by Fernandes et al (2017) in ice cream made with cassava derivatives as fat substitutes. The overrun value can be corrected by the injection of air during the manufacturing Vol.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Although the vegan formulations did not show a significant difference between them (P ࣘ 0.05), they differed from the traditional and lactose-free formulations, being below the required levels, with overrun values ranging from 41 and 42%. Lower overrun values were found by Fernandes et al (2017) in ice cream made with cassava derivatives as fat substitutes. The overrun value can be corrected by the injection of air during the manufacturing Vol.…”
Section: Resultsmentioning
confidence: 80%
“…A lower melting rate was observed in the vegan formulations, which did not differ from each other (P ࣘ 0.05) but were different from the milk-based samples. The use of cassava starch may have interfered with the melting rate, as described by Fernandes et al (2017), who reported that the use of cassava derivatives for fat substitution prolonged the melting time of frozen dessert formulations. Among the traditional and lactose-free samples, a higher melting rate was observed for the sucrose-sweetened samples (TSAC and LFSAC), differing from those sweetened with sweeteners.…”
Section: Texture Analysismentioning
confidence: 99%
“…The disadvantage in the production of sorbets is the use of artificial food additives (structure-forming agents, thickeners, coloring, flavor enhancers, etc.) [14][15][16]. Sorbets are frozen and stored at −18 ºC.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Sorbets are traditionally produced of fresh fruit-vegetable raw materials and also puree, juices without using milk [1][2][3]. A shortcoming at producing sorbets is the use of artificial food supplements (stabilizers, stiffeners, emulsifiers, synthetic coloring agents and so on) [4][5][6]. Freezing and storage of sorbets take place at -18 °С.…”
Section: Introductionmentioning
confidence: 99%
“…Freezing and storage of sorbets take place at -18 °С. This method allows to get high-quality sorbets, which storage term is 10 months [6,7]. But the essential amount of BAS (20-50 %) is lost at defrost and storage.…”
Section: Introductionmentioning
confidence: 99%